Effect of foliar spray with the nutrient elements and organic compound on the qualitative characters of spinach Spinacea oleracea L - Al-Jebouri, K. A. A.; .AL-Ansari, H. R.M (Journal of Kerbala for Agricultural Sciences, 2014)
This study was carried out in the vegetable farm , Department of Horticulture , College of Agriculture , University of Baghdad , during the growing season 2012-2013 .to investigate the effects of two factors on spinach(spinaceaoleraceaL ) . The first is the foliar spray of mixture of ( Mg + Fe + Zn ) at three concentration : A0 ( 0 : 0 : 0 ) , A1 (2.5 : 1.25 : 0.5 ) , A2 ( 5 : 2.5 : 1 ) g.L-1 in the form of sulfates of each element . The second factor ( B ) included foliar spray of four organic compounds : Salicylic acid at 50 mg.L-1 ( B1) , Ascorbic acid at 250 ppm ( B2) , Humic acid at 0.75 ml.L-1 ( B3) , sea weed extract ( ANE ) at 1ml.L-1( B4) and the control ( foliar spray with water ) . The foliar spray with ANE and humic acid significantly increased the percentage of the sugar to 14.71% and 14.64% respectively . Humic acid gave the highest percentage of protein 2.20% . The level A2 gave the highest sugar percentage 14.33% and protein percentage of 2.28% .The interaction of A2 B3 gave the highest sugar percentage 15.35% and protein 2.50% . The foliar spray with organic compound reduced the nitrate percentage to 0.24% in humic acid ANE , the oxalate to 76.93 mg.100mg-1(FW) in ANE . The nitrate percentage was increased as the concentration of mineral used increased and it was 0.31% of A2 level and the oxalate was increased to 87.21 mg.100g-1 ( F.W ) in the level A2 . The intraction A 0B3 significantly decreased the nitrate percentage to 0.21% as compared with the highest percentage 0.37% in A 2B0 , while A 0B 4 significantly decreased oxalate to 74.82 mg.100g-1 (F.W) as compared with the highest content 92.27 mg.100g-1(F.W) in A 2B0 . Flowering set in plants led to reduction the percentage of sugar while the percentage of nitrate was increased as well as the oxlate content increased segnificantlly in leaves to 98.57 mg.100g-1 (F.w) .